GRB2 Links Signaling to Actin Assembly by Enhancing Interaction of Neural Wiskott-Aldrich Syndrome Protein (N-WASp) with Actin-related Protein (ARP2/3) Complex - Carlier, Marie-France; Nioche, Pierre; Broutin-L'Hermite, Isabelle; Boujemaa, Rajaa; Le Clainche, Christophe; Egile, Coumaran; Garbay, Christiane; Ducruix, Arnaud; Sansonetti, Philippe; Pantaloni, Dominique (The Journal of biological chemistry, 2000)
Proteins of the Wiskott-Aldrich Syndrome protein (WASp) family connect signaling pathways to the actin polymerization-driven cell motility. The ubiquitous homolog of WASp, N-WASp, is a multidomain protein that interacts with the Arp2/3 complex and G-actin via its C-terminal WA domain to stimulate actin polymerization. The activity of N-WASp is enhanced by the binding of effectors like Cdc42-guanosine 5′-3-O-(thio)triphosphate, phosphatidylinositol bisphosphate, or the Shigella IcsA protein. Here we show that the SH3-SH2-SH3 adaptor Grb2 is another activator of N-WASp that stimulates actin polymerization by increasing the amount of N-WASp·Arp2/3 complex. The concentration dependence of N-WASp activity, sedimentation velocity and cross-linking experiments together suggest that N-WASp is subject to self-association, and Grb2 enhances N-WASp activity by binding preferentially to its active monomeric form. Use of peptide inhibitors, mutated Grb2, and isolated SH3 domains demonstrate that the effect of Grb2 is mediated by the interaction of its C-terminal SH3 domain with the proline-rich region of N-WASp. Cdc42 and Grb2 bind simultaneously to N-WASp and enhance actin polymerization synergistically. Grb2 shortens the delay preceding the onset of Escherichia coli (IcsA) actin-based reconstituted movement. These results suggest that Grb2 may activate Arp2/3 complex-mediated actin polymerization downstream from the receptor tyrosine kinase signaling pathway.